Carbon dots with multi-functional groups and the application in proton exchange membranes. (10th January 2018) - Jia, Wei; Tang, Beibei; Wu, Peiyi
Abstract: It is of great necessity to achieve a proton exchange membrane (PEM) with high proton conductivity and low methanol permeability for the practical applications. Nafion modified carbon dots (NCDs) with multi-functional groups were successfully synthesized via the pyrolysis of citric acid (CA) with the existence of Nafion. The modification process is motivated by the hydrophilicity-to-hydrophobicity transformation of CA as well as the non-covalent hydrophilic-hydrophobic interaction during the pyrolysis procedure. Multi-functionalized NCDs with moderate hydrophilicity influence the aggregation structure of Nafion matrix of the composite membranes and effectively enhance the high-temperature water retention ability. Both the proton conductivity and the methanol resistance ability of the composite PEMs are significantly enhanced. 0.5-NCD-0.5 Nafion composite PEM presents a 5–10 times increase in proton conductivity and 50% percent decrease in methanol permeability than that of recast Nafion. Graphical abstract: Highlights: Nafion modified carbon dots (NCDs) with multi-functional groups were successfully synthesized. The aggregation structure of the Nafion matrix was adjusted by NCDs. NCD Nafion composite PEMs present a 5–10 times increase in proton conductivity compared to recast Nafion. The methanol permeability of the NCD Nafion composite PEMs is effectively decreased.